Disconnected in a Connected World: Exploring Employee Loneliness in Digital Workplace - Kaur, Sukhmeet; Shukla, Manu; Srivastava, Shaurya (Journal of Emerging Management Studies, 2025)
Purpose - Modern organizations embrace remote work, a digital workplace, and Information and Communication Technology tools to shift their traditional workplace boundaries, leading to unintended adverse outcomes on individual mental and emotional well-being. The study investigates the emerging threat of loneliness in the digitized workplace. Design/methodology/approach - The paper analyzed and combined the Conservation of Resources (COR) theory and the Regulatory Loop of Loneliness theory to comprehend loneliness in a digitalized workplace. Furthermore, the study analyzed existing theories and literature on loneliness and the digital workplace to propose the displacement and stimulation hypothesis. Findings and Conclusion - A supportive workplace, emotional intelligence, social support, self-awareness, self-identity goals, and value well-being can foster engagement and prevent social threats. The study suggests that organizations should foster a balance between organizational resources and outcomes to ensure and prevent loneliness at the workplace. The study is grounded in the theoretical framework of conservation of resources and the loop of loneliness theory, both applicable in the digital workplace. Implications - Even though one cannot separate the physical world from a digitalized work setting, the individual should sense the need for the right resources and practice. The proposed framework applies to virtual settings where humans use electronic resources to connect, communicate, and collaborate. Originality/value - The proposed digitalized workplace loneliness model articulates the original understanding of electronic resources in modern-day loneliness.